Use of 1, 2, 4-triazolo[1, 5-a]pyrimidines to design new "piano-stool" ruthenium(II) compounds. (18th April 2016) - Łakomska, Iwona; Stefańczak, Krystian; Fandzloch, Marzena; Sitkowski, Jerzy; Filip-Psurska, Beata; Wojtczak, Andrzej
Graphical abstract: Neutral half-sandwich organometallic ruthenium(II) complexes of the general formula [(η 6 -p-cym)Ru(L)Cl2 ], where η 6 -p-cym – p-cymene, was prepared by the direct reaction of a dichloride p-cymene ruthenium(II) dimer, [{(η 6 -p-cym)Ru(μ-Cl)}2 Cl2 ], with corresponding 1, 2, 4-triazolo[1, 5 -a ]pyrimidine ligands (L), namely, L-1, 2, 4-triazolo[1, 5- a ]pyrimidine (tp) (1 ), 5, 7-dimethyl-1, 2, 4-triazolo[1, 5- a ]pyrimidine (dmtp) (2 ), 5, 7-ditertbutyl-1, 2, 4-triazolo[1, 5- a ]pyrimidine (dbtp) (3 ), 7-isobutyl-5-methyl-1, 2, 4-triazolo[1, 5- a ]pyrimidine (ibmtp) (4 ), and 5, 7-diphenyl-1, 2, 4-triazolo[1, 5- a ]pyrimidine (dptp) (5 ). The complexes were prepared in molar ratios of 1:2 (except (1 ), for which an excess of tp was used). The structures of the complexes were determined by multinuclear magnetic resonance ( 1 H, 13 C, 15 N) spectroscopy and X-ray diffraction. According to all the spectroscopic data, the molecules adopted the usual "piano-stool" geometry with a monodentate N3 triazolopyrimidine ligand. Studies on these lipophilic ruthenium(II) complexes revealed rather low in vitro antiproliferative activities against two human cell lines. Abstract: A series of neutral half-sandwich organometallic ruthenium(II) complexes of the general formula [(η 6 -p-cym)Ru(L)Cl2 ], where η 6 -p-cym – p-cymene, was prepared by the direct reaction of a dichloride p-cymene ruthenium(II) dimer, [{(η 6 -p-cym)Ru(μ-Cl)}2 Cl2 ], with corresponding 1, 2, 4-triazolo[1, 5 -a ]pyrimidine ligands (L), namely, L-1, 2, 4-triazolo[1, 5- a ]pyrimidine (tp) (1 ), 5, 7-dimethyl-1, 2, 4-triazolo[1, 5- a ]pyrimidine (dmtp) (2 ), 5, 7-ditertbutyl-1, 2, 4-triazolo[1, 5- a ]pyrimidine (dbtp) (3 ), 7-isobutyl-5-methyl-1, 2, 4-triazolo[1, 5- a ]pyrimidine (ibmtp) (4 ), and 5, 7-diphenyl-1, 2, 4-triazolo[1, 5- a ]pyrimidine (dptp) (5 ). The complexes were prepared in molar ratios of 1:2 (except (1 ), for which an excess of tp was used). The structures of the complexes were determined by multinuclear magnetic resonance ( 1 H, 13 C, 15 N) spectroscopy and X-ray diffraction. According to all the spectroscopic data, the molecules adopted the usual "piano-stool" geometry with a monodentate N3 triazolopyrimidine ligand. Studies on these lipophilic ruthenium(II) complexes revealed rather low in vitro antiproliferative activities against two human cell lines.